88 THREE-YEAR FOLLOW-UP OF AN ORAL HEALTH PROMOTION PARTNERSHIP FOR ABORIGINAL CHILDREN IN A REMOTE BRITISH COLUMBIA COMMUNITY. Issue 1 (1st January 2007) - Rozmus, J.; Yeung, A.; Cannon, W. G.; Harrison, R.; Macnab, A. J.
Abstract : Background: Caries is the most common infectious disease and chronic health condition affecting children. Caries and periodontal disease are associated with increased incidence of diabetes, heart disease, stroke, and premature labor in adult life. Prevention programs have had little success in achieving a sustained improvement in the oral health of aboriginal children. Methods: A remote aboriginal community and our Pediatric Residency Program formed a partnership to develop a school-based oral health intervention involving daily classroom brush-ins, regular age-appropriate topical fluoride application, oral health education, and community awareness. Follow-up data were compared for children caries free; decayed, missing, and filled surface (DMFS) scores; and brushing and nutrition. Results: All 58 school-age children were recruited; 26 children had prestudy dental examinations and 42 were examined after 3 years. Conclusions: A combination of great community commitment and educational/health check visits resulted in conscientious adherence to the protocol. The incidence of caries-free children rose significantly at year 1, and at year 3, this improvement has been sustained, along with increased child and parent awareness of good oral health practices and reported improvement in nutrition practices. This school-based program serves as a model that other committed aboriginal communities could readily adopt. The level of involvement by a pediatric residency program may be difficult to duplicate due to costs related to travel to remote communities.